USE OF ADVANCED FOREIGN EXPERIENCES IN INCREASING THE ATTRACTIVENESS OF THE INVESTMENT ENVIRONMENT (World Economics and Finance Bulletin, 2025)
This article examines the importance of increasing the attractiveness of the investment climate for attracting foreign investment to the economy. The experience of the People's Republic of China and Singapore in attracting foreign investment to improve the country's investment climate and their use in Uzbekistan is considered. It also analyzes the latest trends in attracting foreign investment to our country